Odpowiedzi

2010-02-22T20:45:33+01:00
A)
-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
x-4=5x+4
x-5x=4+4
-4x=8 |:(-4)
x=-2

b)
-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x-11=-2
-3x=-2+11
-3x=9 |:(-3)
x=-3
2010-02-22T20:46:51+01:00
A) -x-3 + 2x-1 = 1+4x+3+x
-x+2x-4x-x=1+3+3+1
-4x=8/:(-4)
x=-2

b)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+3+8
-3x=9/:(-3)
x=-3
Najlepsza Odpowiedź!
2010-02-22T20:50:39+01:00
A)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+3+1
2x-6x=8
-4x=8|:(-4)
x=-2

b)-(x+3)- (2x+8) = ( -3-2x) + (2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+3+8
-3x=-3+12
-3x=9|:(-3)
x=-3